2007
DOI: 10.1007/s00534-006-1201-6
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of the greater omentum for prevention of delayed gastric emptying after left hepatectomy with lymphadenectomy for cholangiocarcinoma

Abstract: Fixation of the greater omentum to the peritoneum decreases the occurrence of DGE and other complications after left hepatectomy with lymphadenectomy for cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
1
26
1
1
Order By: Relevance
“…DGE has a variety of causes, including diabetes, renal failure, liver cirrhosis, connective tissue disorders, central nervous system disorders, and surgery. DGE is frequently observed after pylorus-preserving Table 2 Outcomes of 42 patients undergoing hepatic lateral segmentectomy with or without fixation procedure N-G naso-gastric tube, EDGE early delayed gastric emptying a Significant difference pancreaticoduodenectomy, and left-sided hepatectomy also occasionally leads to DGE [2,3]. Displacement of the stomach and the disruption of normal gastrointestinal movement at the points of adhesion between the stomach and the cut surface of the liver are the most probable causes of DGE after left-sided hepatectomy without lymphadectomy [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DGE has a variety of causes, including diabetes, renal failure, liver cirrhosis, connective tissue disorders, central nervous system disorders, and surgery. DGE is frequently observed after pylorus-preserving Table 2 Outcomes of 42 patients undergoing hepatic lateral segmentectomy with or without fixation procedure N-G naso-gastric tube, EDGE early delayed gastric emptying a Significant difference pancreaticoduodenectomy, and left-sided hepatectomy also occasionally leads to DGE [2,3]. Displacement of the stomach and the disruption of normal gastrointestinal movement at the points of adhesion between the stomach and the cut surface of the liver are the most probable causes of DGE after left-sided hepatectomy without lymphadectomy [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…DGE is frequently observed after pylorus-preserving Table 2 Outcomes of 42 patients undergoing hepatic lateral segmentectomy with or without fixation procedure N-G naso-gastric tube, EDGE early delayed gastric emptying a Significant difference pancreaticoduodenectomy, and left-sided hepatectomy also occasionally leads to DGE [2,3]. Displacement of the stomach and the disruption of normal gastrointestinal movement at the points of adhesion between the stomach and the cut surface of the liver are the most probable causes of DGE after left-sided hepatectomy without lymphadectomy [3,4]. Umeshita et al [7] reported that two liver donors in whom DGE occurred because of adhesion between the stomach and the cut surface of the liver after left-sided hepatectomy required surgical division of the adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to 2 RCTs, the use of omentum flap to cover the liver cut surface after left-sided hepatectomy reduced the incidence of DGE [101,102].…”
Section: Prevention Of Delayed Gastric Emptyingmentioning
confidence: 99%
“…Two external drainage catheters (19-Fr BLAKE Silicone Drain) were positioned at the cut surface of the liver and connected to the J-VAC Suction Reservoir. Fixation of the greater omentum was performed to avoid delayed gastric emptying [4] . After operation, major bile leakage occurred, but resolved gradually.…”
Section: Introductionmentioning
confidence: 99%